2013
DOI: 10.1111/head.12103
|View full text |Cite
|
Sign up to set email alerts
|

Symptoms Predictive of Postural Tachycardia Syndrome (POTS) in the Adolescent Headache Patient

Abstract: While no single clinical symptom or headache type reliably establishes the POTS diagnosis, several symptoms can help to distinguish the POTS patient in an adolescent headache population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 27 publications
0
13
0
Order By: Relevance
“…102 -104 In a study of adolescent headache patients in a tertiary-care setting, 53% had POTS. 105 Although headache can be a symptom of OI, the relationship is unclear. The treatment of POTS has been found to be only partially effective in relieving headache.…”
Section: Immune Mechanismsmentioning
confidence: 99%
“…102 -104 In a study of adolescent headache patients in a tertiary-care setting, 53% had POTS. 105 Although headache can be a symptom of OI, the relationship is unclear. The treatment of POTS has been found to be only partially effective in relieving headache.…”
Section: Immune Mechanismsmentioning
confidence: 99%
“…88,89 Approximately two-thirds of patients with chronic daily headache have dizziness, and two-thirds of patients with POTS have headaches. Sometimes it is difficult to differentiate what symptoms the headache disorder is causing, and what symptoms should be attributable to POTS.…”
Section: Potsmentioning
confidence: 99%
“…A recent study demonstrated that 53% of adolescent subjects with headache met criteria for the syndrome through tilt-table testing [6]. It was not surprising that our sample identifi ed headache as the most prevalent type of chronic pain encountered.…”
Section: Discussionmentioning
confidence: 67%
“…The link between POTS, the symptom of pain, and chronic pain syndromes has been discussed in many recent studies and reviews [6][7][8]. Chronic pain syndromes that are often related to a diagnosis of POTS are headache and migraine, functional abdominal pain syndromes, and fi bromyalgia [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation